Journal of the International Neuropsychological Society (Cambridge)
JINS is the official journal of the International Neuropsychological Society, an organization of over 3,700 international members from a variety of disciplines. Our editorial board is comprised of internationally known experts with a broad range of interests. JINS publishes empirically-based articles covering all areas of neuropsychology and the interface of neuropsychology with other areas, such as cognitive neuroscience. Theoretically driven work that has clinical implications is of particular interest.
Keywords: Psychology